Epac1 links prostaglandin E2 to β-catenin-dependent transcription during epithelial-to-mesenchymal transition - Jansen, Sepp R.; Wieland, Thomas (OncoTarget, 2016)
In epithelial cells, β-catenin is localized at cell-cell junctions where it stabilizes adherens junctions. When these junctions are disrupted, β-catenin can translocate to the nucleus where it functions as a transcriptional cofactor. Recent research has indicated that PGE2 enhances the nuclear function of β-catenin through cyclic AMP. Here, we aim to study the role of the cyclic AMP effector Epac in β-catenin activation by PGE2 in non-small cell lung carcinoma cells. We show that PGE2 induces a down-regulation of E-cadherin, promotes cell migration and enhances β-catenin translocation to the nucleus. This results in β-catenin-dependent gene transcription. We also observed increased expression of Epac1. Inhibition of Epac1 activity using the CE3F4 compound or Epac1 siRNA abolished the effects of PGE2 on β-catenin. Further, we observed that Epac1 and β-catenin associate together. Expression of an Epac1 mutant with a deletion in the nuclear pore localization sequence prevents this association. Furthermore, the scaffold protein Ezrin was shown to be required to link Epac1 to β-catenin. This study indicates a novel role for Epac1 in PGE2-induced EMT and subsequent activation of β-catenin.
Gesehen am 08.07.2019
Im Titel ist die Zahl "2" tiefgestellt